Altered mitochondrial lymphocyte in overweight schizophrenia patients treated with atypical antipsychotics and its association with cognitive function - Zhang, Yaoyao; Tang, Wei; Tang, Bei; Fan, Kaili; Zhao, Ke; Fang, Xinyu; Lin, Hui (Frontiers in Immunology, 2024)
Objective Increasing evidence indicated that schizophrenia and obesity are associated with altered mitochondrial and immune function. In this study, we investigated the levels of CRP (C-reactive protein) and mitochondrial lymphocytes in chronically treated schizophrenia patients with atypical antipsychotic medications and further explored the relationship between mitochondrial lymphocyte and weight gain as well as cognitive function in these patients. Methods We evaluated the mitochondrial lymphocyte count of 97 patients (53 overweight, 44 non-overweight) and 100 healthy controls using mitochondrial fluorescence staining and flow cytometry (NovoCyte, Agilent Technologies, US). The serum CRP was measured by high-sensitivity enzyme-linked immunosorbent assay (ELISA). Clinical symptoms and cognitive function of the patients were assessed using the Positive and Negative Syndrome Scale (PANSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Results The results showed that mitochondrial lymphocyte counts of CD3+ T, CD3+CD4+ T, and CD3+CD8+ T cells in schizophrenia patients were higher than in the control group (p < 0.05). Additionally, overweight patients had significantly higher mitochondrial lymphocyte counts of CD3+ T and CD3+CD4+ T cells compared to schizophrenia patients with normal weight. Stratified analysis by gender revealed that there was a statistically significant difference in CD3+CD4+ mitochondrial lymphocyte count in male patients (p = 0.014) and a marginal trend toward significance in female patients (p = 0.058). Furthermore, the mitochondrial lymphocyte counts of CD3+ T and CD3+CD4+ T cells, as well as CRP levels, were positively correlated with BMI in schizophrenia patients, but the mitochondrial lymphocyte counts of CD3+CD4+ T cells were negatively correlated with the language scale in the RBANS. Conclusion Our study results provide evidence for the association between altered mitochondrial T lymphocyte and weight gain as well as cognitive impairment in schizophrenia patients treated with atypical antipsychotic medications.